2013
DOI: 10.1371/journal.pone.0070937
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Differentiation of Monocyte-Derived Dendritic Cells by Human Gingival Fibroblasts

Abstract: We investigated whether gingival fibroblasts (GFs) can modulate the differentiation and/or maturation of monocyte-derived dendritic cells (DCs) and analyzed soluble factors that may be involved in this immune modulation. Experiments were performed using human monocytes in co-culture with human GFs in Transwell® chambers or using monocyte cultures treated with conditioned media (CM) from GFs of four donors. The four CM and supernatants from cell culture were assayed by ELISA for cytokines involved in the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
(41 reference statements)
3
15
0
Order By: Relevance
“…Physiological levels of these growth factors are critical for ensuring wound healing [40]. Recently, Séguier et al showed in vitro that the immunomodulatory effects of GFs involve VEGF secretion [21]. We showed here that VEGF, FGF7, and EGF were overexpressed earlier in GF-treated skin than in MSCtreated skin.…”
Section: Figsupporting
confidence: 50%
See 3 more Smart Citations
“…Physiological levels of these growth factors are critical for ensuring wound healing [40]. Recently, Séguier et al showed in vitro that the immunomodulatory effects of GFs involve VEGF secretion [21]. We showed here that VEGF, FGF7, and EGF were overexpressed earlier in GF-treated skin than in MSCtreated skin.…”
Section: Figsupporting
confidence: 50%
“…The mechanism of GF therapeutic effect on wound healing such as MSC therapy involved inflammatory modulation associated to a switch of macrophages to an M2-like phenotype and an ECM remodeling is reinforced by previous observations where GF secretion factors inhibited dendritic cell differentiation [21].…”
Section: Figmentioning
confidence: 79%
See 2 more Smart Citations
“…As major producers of the extracellular matrix, they control the trafficking of T cells from the invasive margin (IM) to the tumor stroma (Salmon et al, 2012). Fibroblasts can directly inhibit TNF-α and IFN-γ-mediated antitumor immunity (Kraman et al, 2010), hamper DC maturation (Séguier et al, 2013), and inhibit T-cell proliferation (Bocelli-Tyndall et al, 2006;Haniffa et al, 2007;Jones, Horwood, Cope, & Dazzi, 2007). They have been shown to constitutively express the immune checkpoint ligand PD-L1 (Pinchuk et al, 2008), and this expression is upregulated upon IFN-γ stimulation (Pinchuk et al, 2008).…”
Section: Microenvironment-mediated Immunosuppressionmentioning
confidence: 99%